Synergistic Antifungal Effects of Gardenia augusta and Averrhoa bilimbi Leaf Extracts Against Candida albicans: Implications for the Treatment of Oral Candidiasis In Vitro Study - Pande Putu Karina Candra; I Made Jawi; I Gusti Ayu Artini; I Gusti Made Gde Surya Chandra Trapika (HM Publisher, 2024)
Oral candidiasis, commonly known as thrush, is a frequent fungal infection caused by Candida albicans that can lead to painful canker sores and more severe complications. Conventional treatments may have side effects, necessitating the exploration of alternative therapies. This study investigated the antifungal effects of Gardenia augusta and Averrhoa bilimbi leaf extracts against C. albicans in vitro. A post-test-only control group design was employed. Ethanolic extracts of G. augusta and A. bilimbi leaves were prepared. The antifungal activity of individual extracts and their combination (1:1 ratio) was evaluated against C. albicans using the agar well diffusion method. Ketoconazole (2%) served as the positive control, and 96% ethanol was the negative control. The diameter of inhibition zones was measured, and data were analyzed using SPSS version 26.0. Both G. augusta and A. bilimbi leaf extracts demonstrated significant antifungal activity against C. albicans, evidenced by clear inhibition zones. The combination of extracts exhibited a synergistic effect, producing a larger inhibition zone than either individual extract. In conclusion, G. augusta and A. bilimbi leaf extracts hold promise as potential alternative therapies for oral candidiasis. Their synergistic effect suggests a potential for enhanced efficacy in treating canker sores caused by C. albicans. Further research is warranted to explore their clinical application.